Molecular Events Occurring in Lipophagy and Its Regulation in Flaviviridae Infection - Wu, Keke; Fan, Shuangqi; Zou, Linke; Zhao, Feifan; Ma, Shengming; Fan, Jindai; Li, Xiaowen; Zhao, Mingqiu; Yan, Huichao; Chen, Jinding (Frontiers in Microbiology, 2021)
Diseases caused by Flaviviridae have a wide global and economic impact due to high morbidity and mortality. Flaviviridae infection usually leads to severe, acute or chronic diseases, such as liver injury and liver cancer resulting from hepatitis C virus (HCV) infection, dengue hemorrhagic fever (DHF) or dengue shock syndrome (DSS) caused by dengue virus (DENV). Given the highly complex pathogenesis of Flaviviridae infections, they are still not fully understood at present. Accumulating evidence suggests that host autophagy is disrupted to regulate the life cycle of Flaviviridae. Organelle-specific autophagy is able to selectively target different organelles for quality control, which is essential for regulating cellular homeostasis. As an important sub process of autophagy, lipophagy regulates lipid metabolism by targeting lipid droplets (LDs) and is also closely related to the infection of a variety of pathogenic microorganisms. In this review, we briefly understand the LDs interaction relationship with Flaviviridae infection, outline the molecular events of how lipophagy occurs and the related research progress on the regulatory mechanisms of lipophagy in Flaviviridae infection. Exploring the crosstalk between viral infection and lipophagy induced molecular events may provide new avenues for antiviral therapy.